2022
DOI: 10.1038/s41598-022-07711-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of Plasmodium vivax infection among Duffy-negative individuals: a systematic review and meta-analysis

Abstract: A better understanding of the occurrence and risk of Plasmodium vivax infection among Duffy-negative individuals is required to guide further research on these infections across Africa. To address this, we used a meta-analysis approach to investigate the prevalence of P. vivax infection among Duffy-negative individuals and assessed the risk of infection in these individuals when compared with Duffy-positive individuals. This study was registered with The International Prospective Register of Systematic Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Egger’s test was used to assess funnel plot symmetry [ 25 ]. Egger’s test with statistical significance ( p < 0.05) might indicate that funnel plot asymmetry was due to a small-study effect [ 26 ]. A contour-enhanced funnel plot was used to explore the cause (s) of funnel plot symmetry [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Egger’s test was used to assess funnel plot symmetry [ 25 ]. Egger’s test with statistical significance ( p < 0.05) might indicate that funnel plot asymmetry was due to a small-study effect [ 26 ]. A contour-enhanced funnel plot was used to explore the cause (s) of funnel plot symmetry [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A PCR survey of 952 residents of Ghana proved that they were wholly negative for P. vivax [49]. In 2022, Wilairatana et al [50] reported a systematic review and meta-analysis of the prevalence and risk of P. vivax in Duffy-negative individuals.…”
Section: New Evidencementioning
confidence: 99%
“…; Obaldia et al., 2018 ; Silva-Filho et al., 2020 ; Kho et al., 2021 ). There are an increasing number of reports of P. vivax infections now being detected with sensitive tools in Sub-Saharan Africa where it was long thought to have been absent due to the high proportion of Duffy-negative phenotype in the population ( Culleton et al., 2009 ; Oboh et al., 2020 ; Quaye et al., 2021 ; Wilairatana et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies suggest a much more widespread reservoir of P. vivax transmission, with a potential role for extravascular niches where the parasite can survive while it is not detected (Dechavanne et al;Obaldia et al, 2018;Silva-Filho et al, 2020;Kho et al, 2021). There are an increasing number of reports of P. vivax infections now being detected with sensitive tools in Sub-Saharan Africa where it was long thought to have been absent due to the high proportion of Duffy-negative phenotype in the population (Culleton et al, 2009;Oboh et al, 2020;Quaye et al, 2021;Wilairatana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%